Color centers in NaCl single crystals induced by pulsed intense relativistic electron beams to simulate radiation bursts in Europa. (26th March 2019) - Toba, Ryota; Kikuchi, Takashi; Imada, Go; Thorogood, Gordon J.; Hayashi, Naoya; Maynard-Casely, Helen E.; Suematsu, Hisayuki; Nakayama, Tadachika; Suzuki, Tsuneo; Niihara, Koichi
Abstract: To simulate the burst irradiation environment of Europa, single crystals of NaCl were irradiated by pulsed intense relativistic electron beams (PIREBs) with a peak energy of 6 MeV, a current of −800 A, and a pulse width of 70 ns. After irradiation, the optical absorption of the samples was measured, and results indicated that the irradiation induced F- and F2 -centers. The density of F-centers was estimated to be 8.9 × 10 16 cm −3 from 1 shot of PIREB irradiation with 6 MeV. The absorbed energy to form F-centers by PIREB was comparable but slightly higher than those induced by conventional direct current accelerators. The effect of pulsed heating, which should be taken into account for the detection of NaCl on Europa, is discussed.